Caracterização estrutural do domínio interno da faixa Paraguai na região de Cangas, porção centro-sul do estado de Mato Grosso - Costa, Bruno de Siqueira (2014)
The present work aims the structural characterization of Cuiabá Group in the region of Cangas, including descriptions of the quartz veins, which may or may not carry gold mineralization. The geological mapping of a gold mine in the region, allowed the identification of primary structures and three (3) phases of deformation. The primary structures, represented by the sedimentary layering are well preserved and can be easily observed primarily by variations in coloring. The main structure related to the first deformation phase is Sn foliation, which is parallel to the sedimentary layering (S0), being more penetrative in filossilicatic rocks with preferential orientation 120/27.. Folds related to the first phase of deformation are recumbent, being drawn by sedimentary layering and having Sn as axial plane. The second phase of deformation is represented by cleavage fracture (Sn +1) oriented 110/68, more penetrative in competent rock. This structure occurs in the axial plane of normal folds open to gentle and asymmetrical. The third phase of deformation acted in research as a set of fractures and faults in the centimetric-decametric sized, which cuts all previous structures and has preferential orientation 35/82. Two families of quartz veins were observed, the first (V1) occurs parallel to S0 and Sn being in its most deformed and are not carriers of mineralization. The second family (V2) occurs filling the Sn+2 fractures and may or may not be carrying gold mineralization.